KENDALA DAN PERSEPSI PESERTA DIDIK SMA NEGERI 1 KELUMPANG BARAT TERHADAP PEMBELAJARAN FISIKA - Muhammad Ali (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2021)
The objectives of this study were (1) to determine the constraints of students on learning Fiska at SMA Negeri 1 Kelumpang Barat. (2) to find out the students' perceptions of learning physics at SMA Negeri 1 Kelumpang Barat, Kabupaten Kotabaru. The method used in this research is quantitative method in descriptive format, descriptive format or can be called qualitative, namely research conducted only to describe actual conditions or events in the field according to the researchers' observations. While the type of research used is descriptive, this descriptive is to make descriptions, to create a systematic, factual, and accurate description of the facts, characteristics, and relationships between the phenomena being investigated. The results of this study indicate the constraints and perceptions of students towards learning physics, for the constraints it can be concluded that the overall result is 44.5% which is categorized as sufficient and for the mean category (the average sought) is said to be weak, namely 31.39 For the conclusion of students' perceptions of learning physics, the percentage is 62.3% categorized as strong and the category of the average value is weak, namely 36.70. Keywords: Obstacles to Learning Physics, Perceptions of Learning Physics.